Sixteenth president-in-waiting Abraham Lincoln and the Springfield dispatches of Henry Villard, 1860-1861 - Villard, Henry 1835-1900 (Southern Illinois University Press, 2018)
"The most noteworthy reporting of German-born Henry Villard dates from late 1860 and early 1861, when he was embedded in Springfield, Illinois, after Abraham Lincoln's election to the presidency and before his inauguration. Michael Burlingame has organized and annotated all of Villard's dispatches from November 1860 to January 1861"...